Coming out for lesbian women: its relation to anxiety, positive affectivity, self-esteem and social support - Jordan, Karen M.; Deluty, Robert H. (Journal of homosexuality)
"Karen M. Jordan; Robert H. Deluty Fonds Suzan Daniel (FSD)"